2021
DOI: 10.1140/epjd/s10053-021-00281-7
|View full text |Cite
|
Sign up to set email alerts
|

Electron ionization of clusters containing the formamide molecule

Abstract: Studies on electron interactions with formamide (FA) clusters promote scientific interest as a model system to understand phenomena relevant to astrophysical, prebiotic, and radiobiological processes. In this work, mass spectrometric detection of cationic species for both small bare and microhydrated formamide clusters was performed at an electron ionization of 70 eV. Furthermore, a comparative analysis of the cluster spectra with the literature-reported gas-phase spectra is presented and discussed, revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Takatsuka [6] has presented a methodology to unify electronic and nuclear quantum wavepacket dynamics in molecular processes including nonadiabatic chemical reactions whereas a R-matrix theory implemented using the pseudostate formalism has been used to calculate elastic and excitation processes in electron interactions with N 2 H and HCO [7]. Suarez-Moreno et al [8] have reported studies on electron interactions with formamide clusters as a model system to understand phenomena relevant to astrophysical, prebiotic and radiobiological processes. Silva and co-workers [9] reported on a joint theoretical-experimental investigation on the elastic and absorption electron collisions with acetaldehyde.…”
Section: New Scientific Insightsmentioning
confidence: 99%
“…Takatsuka [6] has presented a methodology to unify electronic and nuclear quantum wavepacket dynamics in molecular processes including nonadiabatic chemical reactions whereas a R-matrix theory implemented using the pseudostate formalism has been used to calculate elastic and excitation processes in electron interactions with N 2 H and HCO [7]. Suarez-Moreno et al [8] have reported studies on electron interactions with formamide clusters as a model system to understand phenomena relevant to astrophysical, prebiotic and radiobiological processes. Silva and co-workers [9] reported on a joint theoretical-experimental investigation on the elastic and absorption electron collisions with acetaldehyde.…”
Section: New Scientific Insightsmentioning
confidence: 99%